Estudo da secagem do feijão verde (Vigna unguiculata L. Walp) - análise experimental do processo combinado leito fixo/leito de jorro - Medeiros, Uliana Karina Lopes de (2004)
Green bean is considered as one of most traditional Brazilian Northeast dishes. Green beans drying preliminary experiments show that combine processes, fixed-bed/spouted bed, resulted in dehydrated beans with uniform humidity and the recovery of the beans properties after their rehydration. From this assays was defined an initial humidity suited for the spouted bed process. A fixed-bed pre-drying process until a level of 40% humidity gave the best results. The spouted bed characteristic hydrodynamic curves were presented for different beans loads, where changes in the respective beans physical properties were evidenced during the fluidynamic assay, due simultaneous drying process. One 22 factorial experimental design was carried out with three repetition in the central point, considering as entry variables: drying air velocity and temperature. The response variables were the beans brakeage, water fraction evaporated during 20 and 50 minutes of drying and the humidity ratio. They are presented still the modeling of the drying of the green beans in fine layer in the drier of tray and the modeling of the shrinking of the beans of the drying processes fixed-bed and spouted bed